The Role of Trait and State Mindfulness in Cognitive Performance of Male Adolescents - Firth A; Sütterlin S; Lugo R (Psychology Research and Behavior Management, 2023)
Andrea Firth,1,2 Stefan Sütterlin,3,4 Ricardo Lugo4,5 1University Campus Football Business, London, UK; 2Headgame Performance Psychology, London, UK; 3Faculty of Computer Science, Albstadt-Sigmaringen University, Albstadt, Germany; 4Faculty of Health, Welfare and Organisation, Østfold University College, Halden, Norway; 5Estonian Maritime Academy, Tallinn University of Technology, Tallinn, EstoniaCorrespondence: Andrea Firth; Ricardo Lugo, Email andrea@headgame.co.uk; ricardo.g.lugo@ntnu.noPurpose: The number of mindfulness intervention projects is continually increasing. Within the educational environment, mindfulness has purported links to well-being, positive behaviour, educational and cognitive performance. Trait mindfulness is related to rational thinking and better performance in cognitive tests, suggesting that innate mindfulness ability contributes to self-regulation ability and thus the efficacy of mindfulness interventions. The current study investigates whether mindfulness is a moderating factor. It examines correlations between cognitive performance and trait mindfulness. The study investigates the influence of trait mindfulness on the ability of students to enter state mindfulness in an attempt to understand the role both types of mindfulness may have on cognitive performance.Participants and Method: Two-hundred and five male students aged fifteen and sixteen completed the adolescent version of the Mindfulness Awareness Scale, the Cognitive Reflection Test, and the Toronto Mindfulness Scale.Results: Hierarchical regression analysis found that state mindfulness was a predictor of cognitive reflection ability. ANOVA also found that having either trait or state mindfulness predicted higher cognitive reflection scores, but only state mindfulness had a significant effect on cognitive reflection. Trait mindfulness was not a moderating factor.Conclusion: Both state and trait aspects of mindfulness ability influence cognitive performance. Those with higher trait mindfulness ability are better able to enter state mindfulness and thus had better cognitive reflection scores. However, where it is possible to induce state mindfulness into those with low trait mindfulness, CRT scores were also higher although not significantly so.Keywords: trait mindfulness, state mindfulness, cognitive reflection